The Influence Of Leadership Style And Work Motivation On Employee Performance In Lawang District Office - Alfiana Rizky Ramadhany; Yaqub Cikusin; Hayat Hayat (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
The Lawang District Office, Malang Regency is led by a sub-district head who is under and responsible to the Regent through the Regional Secretary. Lawang District Office which is located on Jl. Thamrin No. 2 Lawang District, Malang Regency 65211. This study aims to see whether there is an influence of Leadership Style and Work Motivation on Employee Performance at Lawang District Office. This research method uses quantitative methods. The data collection method is the distribution of questionnaires, documentation and interviews as complementary data. The analytical technique used is multiple linear regression analysis with SPSS 25 program. The results of this study indicate that partially leadership style has a significant and positive effect on employee performance. Work motivation partially has a significant and positive effect on employee performance. Meanwhile, simultaneously leadership style and work motivation have a significant effect on employee performance.